360 Impact of treatment modality on survival of figo stage IIB cervical cancer: a propensity-score matching analysis based on impact of treatment modality on survival of figo stage iib cervical cancer: a propensity-score matching analysis based on surveillance, epidemiology, and end results database. (4th December 2020) - Tu, Hua; Liu, Guochen; Gu, Haifeng; Liu, Zhimin; Xian, Bingna; Chen, Jieping; Jihong, Liu
Abstract : Introduction/Background: Concurrent chemoradiotherapy is the standard of care for FIGO stage IIB cervical cancer. However, there remains a role of surgical treatment in these patients. The aim of this study was to investigate the impact of treatment modality on survival of patients with stage IIB cervical cancer. Methodology: Patients with stage IIB cervical cancer registered in the Surveillance, Epidemiology, and End Results database between 1988 and 2015 were identified and grouped according to their treatment modalities. For patients identified as surgical group, only those receiving both hysterectomy and chemotherapy were included. For patients identified as non-surgical group, only those receiving both beam radiation and chemotherapy were included. A 1:1 propensity score matching (PSM) were performed to adjust the baseline characteristics. Results: A total of 4718 eligible patients were identified, of whom 902 were in the surgical and 3816 in the non-surgical group. Patients undergoing surgery were younger and were more likely to be married, non-Black race, non-squamous cell carcinoma, N1 stage, and have medical insurance, small tumor compared to those receiving non-surgical treatment (P=0.037 for insurance; P<0.001 for all of others). Before PSM, the surgical group showed significantly improved overall survival (OS) compared with the non-surgical group (P=0.005), while the difference in cancer-specific survival (CSS) only approached significance (P=0.084). After PSM, both the differences in OS and CSS between the two groups reached significance (P<0.001, both). In multivariate analysis, the treatment modality was found to be an independent factor for both CSS (hazard ratio [HR]=1.276, 95% confidence interval [CI] 1.084–1.502, P=0.003) and OS (HR=1.312, 95%CI 1.129–1.524, P<0.001). Other independent factors for both OS and CSS included histological type, tumor size and N-stage. Age was an independent factor for OS but not CSS. Subgroup analysis revealed that patients receiving radiotherapy prior to surgery had significantly improved CSS compared with those treated by other modalities (P<0.001), and that the omission of brachytherapy in non-surgical treatment was associated with significantly decreased CSS (P<0.001). Furthermore, for patients with squamous-cell histology, surgical and non-surgical treatments provided similar CSS (P=0.123). However, for patients with non-squamous-cell histology, surgical treatments provided significantly improved CSS compared with non-surgical (P=0.002). Conclusion: The treatment modality has significant impact on survival of patients with stage IIB cervical cancer. Surgical treatment should be preferentially considered in patients with non-squamous-cell histology. Chemoradiotherapy with completion surgery may be the most effective treatment. However, when non-surgical treatment was selected, the omission of brachytherapy should be avoided. Disclosures: The authors declare that they have no competing interests.